2016
DOI: 10.1179/1743284715y.0000000127
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures and liquid phase separation in multicomponent CoCrCuFeNi high entropy alloys

Abstract: The microstructures of high entropy alloys of the system CoCrCuFe xNi and CoCrCuFeNi x (where x indicates the molar ratio, which, where not specified, is 1) have been investigated. Many Cu rich spheres were evident in the microstructure of CoCrCuFe0.5Ni and CoCrCuFeNi0.5 alloys, which indicates that liquid phase separation had occurred before solidification. During liquid phase separation, the original liquids separated into two liquids: Cu rich and Cu depleted. In contrast, in other alloys ( x = 1.0, 1.5 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 15 publications
2
18
0
3
Order By: Relevance
“…An induction melting study by Wu et al involving CoCrCuFeNi demonstrated the first occurrences of LPS in this alloy [ 116 ]. In Wu’s study, several combinations of the CoCrCuFeNi alloy with varied Fe and Ni were studied to investigate the effects on the microstructure and crystallography of the system.…”
Section: High-entropy Alloys Exhibiting Liquid Phase Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…An induction melting study by Wu et al involving CoCrCuFeNi demonstrated the first occurrences of LPS in this alloy [ 116 ]. In Wu’s study, several combinations of the CoCrCuFeNi alloy with varied Fe and Ni were studied to investigate the effects on the microstructure and crystallography of the system.…”
Section: High-entropy Alloys Exhibiting Liquid Phase Separationmentioning
confidence: 99%
“…In Wu’s study, several combinations of the CoCrCuFeNi alloy with varied Fe and Ni were studied to investigate the effects on the microstructure and crystallography of the system. When Fe and Ni were varied to create CoCrCuFe Ni and CoCrCuFeNi , spherical Cu-rich separations were observed by post-mortem analysis of the solidified samples [ 116 ]. The authors rationalized that the two alloy compositions with positive mixing enthalpies were too great to be overcome by the entropy of the system, which would thereby lower the overall Gibbs energy of the system in the molten state.…”
Section: High-entropy Alloys Exhibiting Liquid Phase Separationmentioning
confidence: 99%
“…The mechanism for such segregation behavior, however, remains unclear, as there are limited accounts of in-situ research in MPCA solidification. For MPCAs in general, a handful of studies 11,16,17 have employed in-situ XRD to observe solid-state phase transformations under pressure and external stress in MPCAs, but studies that discuss the direct solidification behavior of MPCAs, especially the segregation behavior, are largely limited to postmortem analyses 14,15,[18][19][20][21][22][23][24][25] . Some of these ex-situ investigations 15,22,26 on segregation behavior of Cucontaining MPCAs propose the mechanism of liquid-phase separation to be in play, with the evidence of Cu-rich globular clusters present within the solidified microstructures.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid phase separation (LPS) in CoCrCuFeNi has also been observed during supercooling [ 14 , 15 , 16 , 17 ], or by varying concentrations of Fe/Ni [ 18 , 19 , 20 ]. LPS resulting from additions of Mo [ 9 ] and Sn [ 17 ] has also been investigated.…”
Section: Introductionmentioning
confidence: 99%